Deciphering ‘Food Noise’ in the Era of GLP-1 Receptor Agonists: A Comprehensive Narrative Review of Neurobiological Mechanisms and Clinical Implications for Health Education - Janik, Dominika; Sochocka, Agata; Sikorska , Alicja; Mian , Emil; Zapart , Zuzanna; Szepietowska , Martyna; Nowicka , Nina; Bundyra , Jakub; Gańska , Oliwia Zuzanna; Parda , Julia (Journal of Education, Health and Sport, 2026)
Background: Obesity is a complex metabolic disease where impaired brain-gut communication often manifests as "food noise"—intrusive thoughts about food that drive overeating and hinder weight loss. Aim: The aim of this study is to analyze the phenomenon of "food noise" as a key cognitive pathology in obesity and to assess the effect of GLP-1 receptor agonists on its suppression. Materials and methods: A review of scientific sources (2003–2026) was conducted, covering including PubMed, , Google Scholar Results: Food noise was identified as a measurable cognitive pathology linked to hyperactivity in the default mode network (DMN) and dysregulation in the dopaminergic reward system. Clinical and neuroimaging data confirm that incretin-based therapies, notably GLP-and dual GIP/GLP-1 receptor agonists, effectively silence these signals. They act centrally on the hypothalamus (modulating POMC and AgRP neurons), suppressing both homeostatic and hedonic eating drives. This neurological silencing directly correlates with substantial and sustained weight loss, leading to long-term obesity remission. Conclusions: Effective treatment of obesity requires a multidisciplinary approach aimed at eliminating food noise through pharmacotherapy, CBT-OB psychotherapy, and health education.